Normal motor milestone development for use to promote child care - Mahdin A. Husaini; Abas B. Bahari; Jajah K. Husaini; Yekti Widodo; Heryudarini Harahap; Susi Suwarti; Dewi Purnomosari; Fawziah A. Hadis (Indonesian Pediatric Society, 2010)
Background Motor behavior is an essential aspect of child development, and usually assessed in terms of age of achievement of motor milestone. The early detection of infants experiencing subtle delays in motor maturation can allow early intervention in developmental problems. Intervention can be more effective if delays are identified early. In order to facilitate the identification of early delays, the Center of Nutrition and Foods Research andDevelopment in Bogor has designed a simple tool to monitor the child (aged 3 to 18 months) motor development.Objective To develop an observable of normal gross motor maturation for use to detect deviance or motor delay.Methods A total of 2100 healthy children, aged 3-18 months, from high socio-economic group, in urban and suburban areas, were studied. Body length, weight and motor development were measured on all children. Gross motor development was measured 17 pre selected milestones: lie, sit, crawl, creep, stand Mth assistance, walk with assistance, stand alone, walk alone, and run.Results There were no differences between males and females in the comparison of attainment motor maturation therefore a sex combined curve was developed.Conclusion The curve of normal motor milestone development can be used as a tool to evaluate motor development over time, and/or as a child development card for use in primary health care.